[PP.24.05] GESTATIONAL DIABETES AND DEVELOPMENT OF HYPERTENSION: A STUDY USING AMBULATORY BLOOD PRESSURE MONITORING. (September 2016) - Tandurella, N.; Tavecchia, L.; Agostinis, M.; Mongiardi, C.; Test, L. Robustelli; Moretti, S.; Gadaleta, C.; Grossi, A.; Pierobon, V.; Maresca, A.M.; Guasti, L.; Grandi, A.M.
Abstract : Objective: To evaluate the incidence of arterial hypertension (AH) using ambulatory blood pressure monitoring (ABPM) after a long-term follow-up (average: 9 years) in women with pregnancy complicated by (gestational hypertension, GH) or (preclampsia, PE) or (gestational diabetes, GDM) versus women with uncomplicated pregnancies (UP). Design and method: We retrospectively selected, in the database of our city hospital, 200 women who delivered between 2002 and 2007: 50 with GH, 50 with PE, 50 with GDM, 50 with UP. Exclusion criteria were pre-existing AH and diabetes and previous cardiovascular events. For all women, we obtained family and personal medical history, obstetric and laboratory data both at baseline and at follow-up; ABPM was performed at follow-up in order to establish a possible diagnosis of AH. Results: At baseline and follow-up, groups were not different in age, family history of AH, smoking prevalence, BMI, renal function. GH, GDM and PE groups had higher values of mean 24 h SBP and 24 h DBP than UP group. The diagnosis of hypertension was made in 40% of women in GH group and in 32% of women in GDM group vs 14% in UP group (p = 0.005). Incidence of AH in PE group was higher than in UP group, but the difference did not reach statistical significance. Using a Kaplan-Meier analysis, no difference was found in the incidence of AH between GH, PE and GDM groups. No difference was found in the prevalence of masked hypertension and white coat hypertension in all groups. Conclusions: A pregnancy complicated by GDM gives a significantly higher risk of developing AH later in life, and this risk is not significantly different than that given by PE or GH.